Virtual Learning Professional Development: Moderators and Cognitive Presence - Joannidou, Shaunna; Sime, Julie-Ann (Proceedings of the International Conference on Networked Learning, 2012)
The aim of this research is to examine the interactivity between participants in a Virtual Learning Professional Development (VLPD) course to see how moderating facilitation and strategies, particularly scripting, affect the interactivity and quality of the postings in three different modules which were coded using the Community of Inquiry Framework (Garrison, Anderson & Archer (2000). There were over 500 postings submitted in the investigated discussion forums, and there was a marked increase in the postings of the forums throughout the duration of the course. Upon analysis of the discussion forums Akyol & Garrison’s (2011) metacognition assessment was also considered. The VLPD introduced the instructors to learning about Web 2.0 technologies and the pedagogy of using IT in the classroom by using the technology. The participants were foreign language instructors at tertiary level who teach English, Spanish, French, Italian, Turkish and Russian as a foreign language. The need for such a course is based on the idea that teaching is a life-long learning profession in which further education/training is essential to offer best practices in language teaching today. Moreover, it affords motivation and opportunities of career development for the educator. The course was a bottom-up approach with instructors designing, facilitating and voluntarily participating in the program. The VLPD had the intention of (1) introducing the use of technology in foreign language learning by using technology, (2) offering current professional journal articles as well as set tasks that would increase instructors pedagogical knowledge of the hows and whys in applying web 2.0 technologies in their teaching, (3) allowing the foreign language instructors to share and collaborate on professional knowledge and the co-construction of knowledge, and (4) enhancing professional growth and qualifications in a technology enhanced learning environment in a theoretical framework of social constructivism free from time and place constraints. This investigation of three similar discussion forums in three different modules does confirm that scripting as role assignment is effective in leading participants to achieve cognitive presence as determined through the Community of Inquiry Framework.